Respiratory viral infections in bone marrow transplant patients: insights from a tertiary care hospital in Rawalpindi, Pakistan - Noman Shakoor; Saifullah Khan Niazi; Eijaz Ghani; Raheel Iftikhar; Ali Rathore; Misbah Noor (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the incidence of respiratory viral infections in bone marrow transplant patients. Method: The prospective, descriptive, cross-sectional study was conducted at a tertiary care hospital in Rawalpindi, Pakistan, from September 2019 to August 2020, and comprised respiratory specimens from recipients of haematopoietic stem cell transplant. The specimens were collected in viral transport medium, and were then taken to the Department of Virology. Multiplex polymerase chain reaction was performed on the specimens to ascertain the incidence and prevalence of respiratory viruses. Data was analysed using SPSS 24. Results: Of the 85 subjects, 53(62.35%) were males and 32(37.65%) were females. The overall median age was 20.0 years (interquartile range: 11.0-32.0 years). Respiratory viral infections were detected in 31(36.4%) specimens. Among them, human rhinovirus was detected in 12(38.7%) cases, respiratory syncytial virus in 5(16.1%), influenza A/H3 in 4(13%), human parainfluenza virus-1 in 3(9.7%), adenovirus in 2(6.4%), human parainfluenza virus-3 in 1(3.2%), human parainfluenza virus-4 in 1(3.2%) and human metapneumovirus in 1(3.2%) case. There were 2(6.4%) cases of co-infection. Conclusion: More than one-third recipients of haematopoietic stem cell transplant were found to have respiratory viral infections, highlighting the importance of employing multiplex respiratory polymerase chain reaction in early diagnosis and treatment of such infections. Key Words: Respiratory viral infections, Bone marrow transplantation, Multiplex respiratory PCR, Diagnosis.